The Economic Geology of Iran Mineral Deposits and Natural Resources - Ghorbani, Mansour; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The Economic Geology of Iran is a complete and comprehensive book about mineral deposits, energy and water resources of Iran. Dr. Mansour Ghorbani has travelled to each of the huge variety of locations that feature the resources covered, personally verifying the details of them all. The book starts by describing the geography and physiography of Iran as well as its various climatic regions and the diverse corresponding vegetation. Then the book gives an excellent overview of the geology of the country, followed by the history of mining in Iran up to now. The author describes also the metallogenic and mineralization phases of Iran, its mineral zones and belts, and, more generally, the distribution of mineral deposits in the country. Dr. Ghorbani gives us also an analysis of the position of Iran in terms of global mineral resources, as well as the role that the country$1 (Bs mineral, energy and natural resources play in its overall economy. The book finishes with also provides a complete list of Iranian mineral deposits. This book is a perfect source of information for all students and researchers in the field of geo-science at the university level but also for mining and oil companies that would like to work, invest and get involved in such businesses in Iran. Dr. Mansour Ghorbani is associate Professor at the Shahid Beheshti University (Teheran, Iran) since 1999. He is a expert in Iranian Geology and especially in Iranian metal deposits with more than 30 years of experience in the field and many publications.s
Nature of Iran and its climate -- A summary of Geology in Iran -- History of Mining -- Metallogenic and mineralization phases of Iran -- Metallogeny and distribution of minerals -- Metallogenic and mining provinces, belts and zones of Iran -- The position of Iranian mining industry in the world -- Energy resources, production and consumption in Iran compared with the world -- List of mineral deposits and indications of Iran -- References.
Keywords: Geography; Geology, economic; Mines and mineral resources; Physical geography; Earth Sciences; Economic Geology; Mineral Resources; Physical Geography